2018
DOI: 10.1371/journal.pone.0208203
|View full text |Cite
|
Sign up to set email alerts
|

Risk prediction system for dengue transmission based on high resolution weather data

Abstract: BackgroundDengue is the fastest spreading vector-borne viral disease, resulting in an estimated 390 million infections annually. Precise prediction of many attributes related to dengue is still a challenge due to the complex dynamics of the disease. Important attributes to predict include: the risk of and risk factors for an infection; infection severity; and the timing and magnitude of outbreaks. In this work, we build a model for predicting the risk of dengue transmission using high-resolution weather data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Traditional vector control approaches using larval and container surveys provide an estimate of the number of vectors but they are costly, labor-intensive, and are not feasible to implement for the large area, and are not sustainable in long term [ 2 , 41 , 42 ]. Studies related to vector-borne disease modeling often include the proxies of mosquito breeding or resting sites based on the vector-knowledge reviewed in the literature [ 43 , 44 ], survey data [ 13 ], and Breteau Index [ 15 ]. In this paper, we conducted a proof-of-concept study to determine the effects of outdoor container information detected from geotagged images in risk models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional vector control approaches using larval and container surveys provide an estimate of the number of vectors but they are costly, labor-intensive, and are not feasible to implement for the large area, and are not sustainable in long term [ 2 , 41 , 42 ]. Studies related to vector-borne disease modeling often include the proxies of mosquito breeding or resting sites based on the vector-knowledge reviewed in the literature [ 43 , 44 ], survey data [ 13 ], and Breteau Index [ 15 ]. In this paper, we conducted a proof-of-concept study to determine the effects of outdoor container information detected from geotagged images in risk models.…”
Section: Discussionmentioning
confidence: 99%
“…In Thailand, Thammapalo et al [ 12 ] reported that larval indices are predictive of the risk for dengue virus transmission. Hettiarachchige et al [ 13 ] made use of surveillance data on Aedes aegypti larvae and weather data to build a two-stage risk prediction system for assessing dengue transmission via Aedes aegypti mosquitoes on the island of Taiwan. In another study [ 14 ], the authors monitored and analyzed the adult female Ae .…”
Section: Introductionmentioning
confidence: 99%
“…Hettiarachchige et al (113) built a data transmission risk prediction model based on high resolution meteorological data. Additionally, this risk is predicted through vector prediction.…”
Section: Models Of Mosquitoes Dynamics Breeding Sites Modelsmentioning
confidence: 99%
“…Extra dengue outbreak contribution factors were not taken into consideration and best combination of predictive factors are not identified. The authors in [2] specified the key attributes used to predict dengue such as severity caused due to infection, risk of infection, the timing of dengue and incidence of outbreaks of dengue in a locality. A model was built to predict dengue outbreak based on high resolution weather data.…”
Section: Related Workmentioning
confidence: 99%